APLIKASI E-COMMERCE DAN MANAJEMEN SERVICE (STUDI KASUS : SMARTCOMP STORE OFFICIAL) - Afrizal , Afrizal; Damma, Arnio (JURNAL AKADEMIKA, 2023)
SmartComp is a business engaged in the sale of computer equipment, accessories, and services. The image and prestige in the eyes of the public is enough to raise the name of this business. However, these businesses still have major obstacles in promoting the goods and services they have and added to the limited time and energy because they still use the old way by distributing brochures and installing banners that are expected to attract public attention. But in fact, there are still many people who do not know the types of goods and services offered by SmartComp. The advantages of the new system are that people know what products are in the e-commerce application and can directly order goods and services online without having to come directly to the place where the business is located so as to provide security and comfort in transacting without taking up the time and energy they have.